Principal’s Leadership in Improving Teacher’s Performance in Elementary Schools - Dellyana, Dellyana (PPSDP International Journal of Education, 2024)
This study aims at analyzing principal’s leadership in improving teacher’s performance. Leadership is the ability to encourage a group to achieve a specific goal. Leadership has a great influence on the progress of the organization, and the qualities shown by the leaders. Leaders are often considered the most important element that determines the success of an organization. This study uses qualitative descriptive that aims to analyze the circumstances, conditions, or other things, and the results are documented in the research report. The results stated that the principal has a leadership function as an educator, manager, administrator, supervisor, leader, innovator, and motivator (EMASLIM). Based on observations in schools, the problem found by the researcher is that the principal’s efforts to improve teacher’s performance have not been fully resolved. For example, it still looks low in attendance. Teachers face difficulties in preparing learning plans.